Narratives of Islamic legal theory - Ahmed, Rumee (Oxford : Oxford University Press, 2012)
Rumee Ahmed shatters the prevailing misconceptions of the purpose and form of the Islamic legal treatise. Through a subtle interpretation of the work of major Islamic jurists, he reveals how the moral teachings of Islam were translated into a legal context in the critical, formative period of Islamic law.
Description based on online resource; title from PDF title page (viewed on Apr. 18, 2012).
Includes bibliographical references and index.
Keywords: Islamic law -- Interpretation and construction